Construction for a sustainable environment : proceedings of the International Conference of Construction for a Sustainable Environment, Vilnius, Lithuania, 1-4 July, 2008 /: proceedings of the International Conference of Construction for a Sustainable Environment, Vilnius, Lithuania, 1-4 July, 2008. (2010) - Unknown
No abstract available